Radiofrequency Ablation of a Left Atrial Appendage Tachycardia on ECMO Support - Mohsin Khan; Andre Gauri; Ronald Grifka; Darryl Elmouchi (Hindawi Limited, 2013)
Extracorporeal membrane oxygenation (ECMO) has been utilized in the pediatric population for cardiogenic shock secondary to medically intractable arrhythmias. There is limited experience with cardiac radiofrequency ablation (RFA) on these patients while on ECMO. A 7-year-old girl presented with a tachycardia-mediated cardiomyopathy secondary to a left atrial appendage tachycardia. She suffered a cardiac arrest due to pulseless electrical activity and was placed on ECMO. Due to elevated left atrial pressures and the refractoriness of her arrhythmia to cardioversion and antiarrhythmic therapy, while on ECMO, blade atrial septostomy and radiofrequency ablation were performed. The patient tolerated the procedure well and was successfully decannulated. Her cardiac function normalized within four weeks of the ablation procedure. Twelve months after the procedure, she remains completely well, with no symptoms or tachycardia.